2007
DOI: 10.1186/1471-2431-7-26
|View full text |Cite
|
Sign up to set email alerts
|

Community health and medical provision: impact on neonates (the CHAMPION trial)

Abstract: Background: The trial aims to evaluate whether neonatal mortality can be reduced through systemic changes to the provision and promotion of healthcare. Neonatal mortality rates in India are high compared to other low income countries, and there is a wide variation of rates across regions. There is evidence that relatively inexpensive interventions may be able to prevent up to 75% of these deaths. One area with a particularly high rate is Mahabubnagar District in Andhra Pradesh, where neonatal mortality is esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…The trial was conducted in villages with a population of less than 2,500 people in the Nagarkurnool division in the state of Andhra Pradesh in India which were participating in the CHAMPION Trial [12]. All children living in these villages who were potentially eligible for the trial were listed in January 2008, before the randomisation for the Champion trial.…”
Section: Methods and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The trial was conducted in villages with a population of less than 2,500 people in the Nagarkurnool division in the state of Andhra Pradesh in India which were participating in the CHAMPION Trial [12]. All children living in these villages who were potentially eligible for the trial were listed in January 2008, before the randomisation for the Champion trial.…”
Section: Methods and Outcomesmentioning
confidence: 99%
“…The consent process initially followed that for the CHAMPION Trial [12] and is described in the trial protocol [13]. Approval of the protocol was obtained from the Department of Education of the Government of Andhra Pradesh.…”
Section: Methods and Outcomesmentioning
confidence: 99%
“…mobile teams providing antenatal and postnatal care in the home or through fixed day health services), and provision of facility-based care (i.e. subsidised access to non-public health centres) [18]. The primary outcome of neonatal mortality was significantly lower in the intervention arm compared to the control arm (52 neonatal deaths per 1000 live births versus 69 deaths per 1000 live births), a reduction of 24% (relative risk 0.76; 95% CI 0.64 to 0.90; p = 0.0018).…”
Section: Background and Rationale {6a} Champion2mentioning
confidence: 99%
“…mobile teams providing antenatal and postnatal care in the home or through fixed day health services), and provision of facility-based care (i.e. subsidised access to non-public health centres) [18]. The primary outcome of neonatal mortality was significantly lower in the intervention arm compared to the control arm (52 neonatal deaths per 1000 live births vs. 69 per 1000 live births), a reduction of 24% (Relative Risk 0.76; 95% CI 0.64 to 0.90; p=0.0018).…”
Section: Championmentioning
confidence: 99%
“…The primary outcome of neonatal mortality was significantly lower in the intervention arm compared to the control arm (52 neonatal deaths per 1000 live births vs. 69 per 1000 live births), a reduction of 24% (Relative Risk 0.76; 95% CI 0.64 to 0.90; p=0.0018). The authors concluded that the CHAMPION intervention was strongly justified in this setting, but the trial needed adaptation and further development for evaluation in other areas [18].…”
Section: Championmentioning
confidence: 99%